Fluorinated phosphonate analogues of phenylalanine – synthesis, structural studies and reactivity - Kwiczak, Joanna Marianna (My University, 2017)
α-Aminophosphonates containing in their structure fluorine atom(s) are bioactive compounds. Due to their biological and pharmacological activities, they have found a wide range of applications in medicinal and agricultural chemistry. First aim of the doctoral dissertation was the synthesis and structural characterization of phosphonate analogues of phenylalanine containing in the phenyl ring different number of fluorine atoms, as potential inhibitors of aminopeptidase. α-Aminophosphonates were synthesized by one-pot two steps reaction. First, imine was generated, followed by the nucleophilic addition of diethyl phosphite. What is more, a convenient method for the synthesis of fluorinated aldehydes, which were not commercially available, was developed. In this work, novel monodeprotection method of diethyl phosphonate group by LiI leading to corresponding monosalt, and deprotection by Me3SiBr resulted in aminophosphonic acid, were developed. Additionally, reactivity of α-aminophosphonates towards aromatic nucleophilic substitution was studied. A large library of para substituted fluorinated analogues of phenylalanine was synthesized in the reactions with different nucleophiles such as thiolates, amines and phenolates.

W ostatnich latach coraz większe znaczenie zyskuje synteza fluorowanych pochodnych aminofosfonianów. Fluorowane aminofosfoniany wykazują działanie przeciwnowotworowe, przeciwwirusowe, przeciwbakteryjne ponadto, mogą również działać jako inhibitory enzymów. Celem niniejszej rozprawy było zsyntezowanie fosfonianowych analogów fenyloalaniny zawierających w swojej strukturze różną ilość atomów fluoru znajdujących się w różnych pozycjach pierścienia aromatycznego. Celem było również przeprowadzenie badań reaktywności otrzymanych analogów. Uzyskane aminofosfoniany mogą być potencjalnymi inhibitorami aminopeptydaz, a ponadto mogą wykazywać działanie przeciwnowotworowe. Fluorowane fosfonianowe analogi fenyloalaniny otrzymano w wyniku reakcji dwuetapowej. W pierwszym etapie wytworzono iminę, a następnie w wyniku nukleofilowej addycji fosforynu dietylu uzyskano α-aminofosfonian. Opracowano metodę syntezy niedostępnych komercyjnie fluorowanych aldehydów, stanowiących substraty w reakcjach otrzymywania aminofosfonianów. Ponadto, opracowano nową metodę monodeprotekcji grupy dietylofosfonianowej z zastosowaniem LiI. W niniejszej pracy przeprowadzono badania reaktywności fluorowanych fosfonianowych analogów fenyloalaniny w reakcjach SNAr. Zsyntezowano bibliotekę para podstawionych związków posiadających perfluorowany pierścień aromatyczny.
Fluorowane fosfonianowe analogi fenyloalaniny – synteza, badania strukturalne i reaktywność
Wydział Chemii
Keywords: α-aminofosfoniany; fluor; deprotekcja fosfonianów; aromatyczna substytucja nukleofilowa; α-aminophosphonates; fluorine; deprotection of phosphonates; nucleophilic aromatic substitution